OPTIMIZING PRODUCTION DECISIONS THROUGH DIFFERENTIAL COST ANALYSIS: A CASE STUDY OF MAKE-OR-BUY STRATEGY IN MANUFACTURING - anggi rizky imania; Diani Naraswari; Gaspar Pandi; Indah Agustin; Ninuk Riesmiyantiningtias (Universitas Tulungagung, 2025)
Increasing competition in the digital printing industry requires companies to optimize production decisions while maintaining cost efficiency and profitability. Although make-or-buy decisions are common in managerial practice, many small and medium-sized manufacturing firms still rely on managerial judgment rather than systematic cost analysis, creating the need for more objective decision-support approaches. This study aims to evaluate the application of differential cost analysis in determining the most economically advantageous production alternative at CV Haza Sarana Kreasi. A descriptive qualitative case study approach was employed using primary data collected through interviews and direct observation. The analysis was based on production cost data, including direct material costs, direct labor costs, manufacturing overhead, external procurement prices, production volume, defective products, and selling prices. Differential cost analysis and profitability analysis were used to compare internal production with external procurement. The findings reveal that the internal production cost was Rp 12,500 per meter, which was lower than the external procurement cost of Rp 13,500 per meter, resulting in a cost advantage of Rp 1,000 per meter. Furthermore, internal production generated a slightly higher net daily profit (Rp 407,500) than external procurement (Rp 405,000), despite losses caused by defective products. These results indicate that internal production is the more economically beneficial alternative for the company. The study demonstrates that differential cost analysis provides an effective managerial accounting tool for supporting make-or-buy decisions by identifying relevant costs and improving production efficiency. The findings offer practical guidance for manufacturing firms seeking to optimize production strategies and contribute to the growing body of knowledge on the application of differential cost analysis in managerial decision-making.